Retrospective Exposure Assessment for Semiconductor and Storage Device Manufacturing Facilities. Issue 4 (April 2019) - Rodrigues, Ema G.; Stewart, James; Herrick, Robert; Palacios, Helena; Laden, Francine; Clark, William; Delzell, Elizabeth
Abstract : Objective: The aim of this study was to develop exposure estimates for a case–control study of central nervous system cancer in semiconductor and storage device manufacturing workers. Methods: Over 700, 000 records on sample measurements were obtained. Mean exposure intensity was estimated for 31 established/suspected carcinogens (agents of interest) in 10 primary exposure groups over three manufacturing eras. We assigned confidence ratings, based on number/type of measurements, to each estimate. Results: Mean exposures decreased by an order of magnitude over the three manufacturing eras and were below applicable occupational exposure limits for 22 of 31 agents of interest. For 25 agents, at least 70% of the exposures were estimated with high confidence. Conclusion: This is the largest comprehensive study of exposures in the semiconductor/storage device industry and the first to include cumulative exposure estimates and measures of confidence in the exposure estimates. Abstract : Supplemental Digital Content is available in the text